Thread of Blood : Colonialism, Revolution, and Gender on Mexico's Northern Frontier - Alonso, Ana María, 1955- (Book collections on Project MUSE., 1995)
"This outstanding volume links the analysis of community and social organization with macro-level processes and history. Examines how gender, ethnicity, and local concepts of power relate to national identity, economy, and power. A fascinating discussion of Mexican society and the revolutionary change occurring along Mexico's northern border"--Handbook of Latin American Studies, v. 57.